Hepatitis B Screening Program for patients attending out-patient department (OPD) at Sir Salimullah Medical College Mitford Hospital, Dhaka – An Observational Study - Md Rashid Un Nabi, Quazi; Karim, Md Fazal; Podder, Provat Kumar; Islam, Mohammad Nasirul; Hossain, Mohammad Shawkat; Bepari, Md Shahin; Gazi, Mohammad Ashraf Hossain (Sir Salimullah Medical College Journal, 2023)
Background: Hepatitis B (HBV) is a major cause of chronic hepatitis, cirrhosis of liver and hepatocellular carcinoma in Bangladesh. It is also the most common cause of death from liver disease in the country. The prevalence of hepatitis B is 5-6% in the general population. So the present status of the virus is considered as an important public health concern of Bangladesh. Objectives: To investigate hepatitis B prevalence among the persons attending the OPD and to increase awareness about hepatitis B. Materials and methods: A cross-sectional observational study was carried out the at the Department of Hepatology, Sir Salimullah Medical College Mitford Hospital, Dhaka on March 17&18, 2022 at Special Treatment Campaign on the occasion of celebration of the birth anniversary of the Father of Nation, Bangabandhu Sheikh Mujibur Rahman. A total of 190 people of both sexes from 18 years to 50 years of age group were enrolled in the study. These people were unaware of whether they were carrying hepatitis B virus or also was not aware of whether they are suffering from any kind of liver disease. Informed consent was taken and a pre-designed structured questionnaire was used. Screening was done by HBsAg detection using rapid diagnostic kit. Result: The mean age of respondents was 35.95±6.42 years with a male to female ratio of 0.83. Most of the respondents were married (72.63%) and Muslim (87.37%). Among them 47.36% of the respondents were service holders. Only 17.89% had a previous history of some types of hepatitis. 25.26% of respondents had history of different types of surgical procedure. 8 (4.2%) participants were found positive for HBsAg on the screening test in our study. Conclusion: This study shows 4.2 % of participants were screening positive among the respondents. This correlate with the intermediate prevalence of hepatitis B in Bangladesh as stated in World Health Organization data. Screening program increases knowledge and awareness among the population and thereby increase treatment seeking, which ultimately reduce incidence of disease and complications as well as death. Sir Salimullah Med Coll J 2023; 31: 3-8